2012
DOI: 10.1534/genetics.112.145128
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Human Brain Coding/Noncoding Gene Regulatory Networks

Abstract: While most gene transcription yields RNA transcripts that code for proteins, a sizable proportion of the genome generates RNA transcripts that do not code for proteins, but may have important regulatory functions. The brain-derived neurotrophic factor (BDNF ) gene, a key regulator of neuronal activity, is overlapped by a primate-specific, antisense long noncoding RNA (lncRNA) called BDNFOS. We demonstrate reciprocal patterns of BDNF and BDNFOS transcription in highly active regions of human neocortex removed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(212 citation statements)
references
References 80 publications
11
201
0
Order By: Relevance
“…The top signal came from the noncoding antisense RNA transcript BDNF-AS locus ( P =6.25E-07) on chromosome 11. BDNF-AS downregulates the BDNF gene 33 which in turn has a key role in regulating neuronal growth and synaptic plasticity 33, 34 . The BDNF gene did not reach genome-wide significance in our gene-based analysis ( P =1.3E-04), result indicating that the eight significant SNPs reported in the combined TAG analysis were tagging better the overlapping non-coding RNA BDNF-AS locus (see Supplementary Figures 35 for LD information).…”
Section: Discussionmentioning
confidence: 99%
“…The top signal came from the noncoding antisense RNA transcript BDNF-AS locus ( P =6.25E-07) on chromosome 11. BDNF-AS downregulates the BDNF gene 33 which in turn has a key role in regulating neuronal growth and synaptic plasticity 33, 34 . The BDNF gene did not reach genome-wide significance in our gene-based analysis ( P =1.3E-04), result indicating that the eight significant SNPs reported in the combined TAG analysis were tagging better the overlapping non-coding RNA BDNF-AS locus (see Supplementary Figures 35 for LD information).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found other similar examples and indeed were able to engineer synthetic lncRNAs to activate translation of a GFP transgene. It is likely that other antisense lncRNAs also bind their sense, coding transcript to effect other regulatory outcomes: BACE1-as binds to and increases the stability of BACE1 mRNA (Faghihi et al 2008), whereas another neural antisense transcript, BDNFOS, negatively regulates BDNF mRNA (Lipovich et al 2012). Both of these transcripts contain multiple exonic TE insertions, although these have not yet been strictly linked to function.…”
Section: Direct Evidence For Te-derived Functional Domains In Lncrnasmentioning
confidence: 99%
“…A significant fraction of these lncRNAs is expressed in the mouse brain, sometimes in an activity-dependent manner, and often within a rather specific spatial or temporal pattern (Lipovich et al, 2012;Mercer et al, 2008). The localization of specific lncRNAs in the synaptic neuropil suggests that they may be involved in the local regulation of gene expression required for synaptic plasticity.…”
Section: New Kids On the Block: Circrnas And Other Lncrnasmentioning
confidence: 99%